2019
DOI: 10.3389/fnins.2018.01001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Co-methylation Relationships Between Rheumatoid Arthritis and Parkinson's Disease

Abstract: Rheumatoid arthritis (RA) is a complex autoimmune disease. Recent studies have identified the DNA methylation loci associated with RA and found that DNA methylation was a potential mediator of genetic risk. Parkinson's disease (PD) is a common neurodegenerative disease. Several studies have indicated that DNA methylation levels are linked to PD, and genes related to the immune system are significantly enriched in PD-related methylation modules. Although recent studies have provided profound insights into the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…KEGG pathway analysis of DEGs demonstrated relatively high enrichment in the pathway concerning Alzheimer disease; although the enrichment in Parkinson disease was less significant, these pathways were strongly correlated with neurodegenerations. Their association with RA was supported by several publications; specifically, a Mendelian randomization study proposed a correlation between RA and Alzheimer disease (Bae and Lee, 2019 ); co-methylation relation study revealed that samples of RA and Parkinson disease shared 337 significantly altered (vs. their respective control) methylation gene pairs (Tang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…KEGG pathway analysis of DEGs demonstrated relatively high enrichment in the pathway concerning Alzheimer disease; although the enrichment in Parkinson disease was less significant, these pathways were strongly correlated with neurodegenerations. Their association with RA was supported by several publications; specifically, a Mendelian randomization study proposed a correlation between RA and Alzheimer disease (Bae and Lee, 2019 ); co-methylation relation study revealed that samples of RA and Parkinson disease shared 337 significantly altered (vs. their respective control) methylation gene pairs (Tang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…Although differential methylation regions (DMRs) in different autoimmune diseases are distinct, numerous of DMRs and pathways are found to be shared by different autoimmune diseases. For example, recent study identified 337 differentially methylated genes are shared by RA and Parkinson's Disease (PD) which provides new evidence for the shared biological mechanism between RA and PD (Tang et al, 2018). Further study find mitochondrial L-carnitine shuttle pathway and PTEN signaling pathway are simultaneously differentially expressed in RA, systemic sclerosis, and SLE (Hudson et al, 2017).…”
Section: Genome-wide Methylation Profiling To Identify Rheumatoid Artmentioning
confidence: 97%
“…To further investigate the relationship between the tumor and normal samples, we examine how the correlation coe cient of each CG pair changes by comparing the normal with the tumor samples. Following the example of a previous publication [17], Table 5 The number of CG pairs whose correlation coe cients fall within certain intervals. ) in the normal data to very high negative correlations ([-1.0, -0.75)) in the tumor data.…”
Section: Highly Changing Cg Pairsmentioning
confidence: 99%